Investigation on Effect Oo Abs Filament Extrusion Process Temperature for Fused Filament Fabrication (FFF) 3D Printing - Fikri, Aziq; Khairu Kamarudin, (Progress in Engineering Application and Technology, 2022)
The study highlighted the effect of temperature on the processing of ABS filaments for Fused Filament Fabrication (FFF) by using a small extruder machine. However, manufacturing filaments with a tiny extruder needs the usage of proper Fused Filament Fabrication parameters (FFF). Filaments available on the market are produced using commercial extruders that equipped with the establish equipment.